Dynamics of spatial monetary policy to achieve sustainable financial developments - Wuri, Josephine (Edelweiss Applied Science and Technology, 2026)
The monetary authority’s policy accuracy is needed to create stability in the global financial sector because countries are currently integrated into the world. The monetary policies of the world’s leading countries influence those of other countries. This study aims to analyze the dynamic spatial effects of monetary policy on financial development between ASEAN+3 countries for the period 2010–2020 and examine whether there is sustainable financial development by considering regulatory quality as a control variable. The study also analyzes the impact of the COVID-19 pandemic on financial development. This study uses a dynamic spatial analysis model to capture spatial interactions, short-term and long-term effects, and obtain consistent parameters, using spatial weights based on distance. The results of the study show that monetary policy has a dynamic spatial spillover effect on financial development, both short-term and long-term. Monetary policy with contractionary lending rates can weaken financial development, and conversely, expansionary policies can encourage financial development so that sustainable financial development can be achieved. Empirical results also show that the COVID-19 pandemic weakened the global financial sector. These findings are robust to alternative model specifications.